2014
DOI: 10.1016/j.contraception.2013.10.017
|View full text |Cite
|
Sign up to set email alerts
|

The IUB, a newly invented IUD: a brief report

Abstract: Objective To evaluate the initial safety and effectiveness of the Intrauterine Ball, a copper intrauterine device which upon insertion in the uterus takes a three dimensional spherical form. Study Design Fifteen women were followed for one year, with follow-up visits at 1, 3, 6, 9, and 12 months. Results The physician reported that all devices were very easy to insert. One subject discontinued before the 6 month visit (at 119 days post insertion) for a reason not related to the device. There were no perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…A recent study 68 described a new IUD -the intrauterine ball -which is postulated to reduce perforation and malposition, and ease insertion. This has only been tested in 15 women, and not for emergency contraception, so common usage is a long way in the future.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study 68 described a new IUD -the intrauterine ball -which is postulated to reduce perforation and malposition, and ease insertion. This has only been tested in 15 women, and not for emergency contraception, so common usage is a long way in the future.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the device is very easy to insert and there were no untoward events such as perforations, expulsions, malpositions, or pregnancies [80].…”
Section: Intrauterine Contraceptionmentioning
confidence: 99%
“…The copper content varies between the different types and sizes available but they are mostly T-Shaped devices. An intrauterine ball (IUB) is currently under investigation: the IUB takes on a 3-dimensional spherical form (Baram et al 2014), whereas the currently marketed devices take on a 2-dimensional shape in the uterus.…”
Section: Intrauterine Devicesmentioning
confidence: 99%